A comparison of gender on leadership styles and its relationship towards organizational commitment - Ting, Siew Ming (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Leadership styles are a very important component for an organization to accomplish their goals and competitiveness and maximize human capital. Employees may prefer different leadership styles and different gender to be their leader in their organization. The main objective of this JUdy was to compare leadership styles of male and female leaders and to see d~fJerent leadership styles whether have a significant impact to organizational commitment. Cross ectional study was used in this research. This is a quantitative study which was conducted in a hypermarket and department store, Kuching, Sarawak. 40 respondents were chosen by using purposive sampling technique to answer the questionnaires. A pilot study was done before the real study was conducted. The instruments used are reliable. The results showed that there is a significance relationship on the comparison of gender and leadership styles and its impact to organizational commitment. It was found that male leader who possessed transformational leadership style had more effectual towards organizational commitment than female leader. Besides, male and female possessed both transformational and also transactional leadership styles. In addition, there is a significant relationship between leadership styles and organizational commitment. Based on the findings, most followers prefer female leader and also transformational leadership styles. All the findings in this study had been supported by the previous studies which related on this topic. It is concluded that leadership styles possessed by the leaders had a Significant effect toward." organizational commitment.